Hypertension and Its Associated Factors Among Long-Distance Truck Drivers in Ethiopia - Rike ME; Diress M; Dagnew B; Getnet M; Hasano Kebalo A; Sinamaw D; Solomon D; Akalu Y (Integrated Blood Pressure Control, 2022)
Mohammed Ebrahim Rike,1 Mengistie Diress,2 Baye Dagnew,2 Mihret Getnet,2 Abbul Hasano Kebalo,1 Derese Sinamaw,3 Damtew Solomon,1 Yonas Akalu2 1Department of Biomedical Science, School of Medicine, College of Medicine and Health Sciences, Madda Walabu University, Bale Robe, Oromia, Ethiopia; 2Department of Human Physiology, School of Medicine, College of Medicine and Health Sciences, University of Gondar, Gondar, Amhara, Ethiopia; 3Department of Biomedical Science, School of Medicine, College of Medicine and Health Sciences, Debre Markos University, Debre Markos, Amhara, EthiopiaCorrespondence: Mohammed Ebrahim Rike, Department of Biomedical Science, School of Medicine, College of Medicine and Health Sciences, Madda Walabu University, Bale Robe, Ethiopia, Tel +251920071361, Email zakiziaa9@gmail.comIntroduction: Hypertension is rising globally and is one of the leading causes of cardiovascular disease. It affects people of different groups; however, owing to a rise in a sedentary lifestyle it is more prevalent among long-distance truck drivers. However, the prevalence of hypertension and its associated factors among truck drivers in Ethiopia is not known. Therefore, this study aimed to determine the prevalence of hypertension and its associated factors among long-distance truck drivers in Ethiopia.Methods: A cross-sectional study was conducted among 415 long-distance truck drivers selected by systematic random sampling technique at Modjo dry port from May 15 to 30, 2021. The data were collected and entered into Epi-data 4.6 then it was exported to SPSS version 25 for analysis. Descriptive statistics, bivariable, and multivariable logistic regression analyses were executed. The odds ratio with a 95% confidence interval was computed. In the final model, a variable with a p ≤ 0.05 was declared as a predictor of hypertension.Results: The prevalence of hypertension among long-distance truck drivers in Ethiopia was 34.7%. The odds of hypertension was higher among drivers who were ≥ 45 years old [Adjusted odds ratio (AOR) = 4.32; 95% Confidence interval (CI): 2.16, 8.62], obese [AOR= 5.12; 95% CI: 1.33, 19.8], alcohol drinkers [AOR=3.05; 95% CI: 1.27, 7.31], and cigarette smokers [AOR= 3.74; 95% CI: 1.64, 8.51]. Drivers who had regular physical exercise were less likely [AOR=0.33; 95% CI: 0.17, 0.63] to have hypertension than drivers with no physical activity.Conclusion: More than a third of the participants in Ethiopia had hypertension. Higher age, obesity, absence of rest between driving, short sleep duration, smoking, alcohol drinking, and physical inactivity were significantly associated with hypertension. Therefore, health education on lifestyle modifications, sleep habits, and the importance of rest breaks between driving should be considered to prevent hypertension and further complications.Keywords: hypertension, long-distance truck drivers, Ethiopia